2021
DOI: 10.2147/lctt.s235102
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Prognostic and Predictive Biomarkers in the Treatment of Non-Small Cell Lung Cancer (NSCLC) with Immune Checkpoint Inhibitors (ICIs)

Abstract: Immunotherapy plays a central role in the treatment of NSCLC and biomarkers predicting response to ICIs are valuable therapeutic tools. Programmed death-ligand 1 (PD-L1) immunohistochemistry (IHC) is integral in therapy selection as its positive predictive nature to ICIs in the metastatic setting is well documented. Tumor mutational burden (TMB) has undergone much study and, while results are somewhat mixed, there is evidence for its positive predictive value with ICI use. Additional markers such as tumor-infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Although some authors have reported a predictive and prognostic role of the neutrophil-to-lymphocyte ratio (NLR) in patients with advanced NSCLC undergoing different systemic treatments, its role in NCSLC patients with BMs has yet to be clarified (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have reported a predictive and prognostic role of the neutrophil-to-lymphocyte ratio (NLR) in patients with advanced NSCLC undergoing different systemic treatments, its role in NCSLC patients with BMs has yet to be clarified (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…However, how to screen the best beneficiaries has always been the focus of immunotherapy research, and the development of biomarkers is one of the major research directions. [ 45 , 46 ] Currently, the ICIs therapy can effectively improve the prognosis of various cancers, and the immune checkpoint expression has become an important indicator of ICIs therapy. [ 47 ] TIDE algorithm is a novel method to predict treatment response to ICIs, which can replace a single biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…14 alteration; 9.7 for BRAF mutation; and 10.3 for KRAS mutation ( p < 0.001 in all groups in Wilcoxon signed-rank test vs. KRAS ). Furthermore, high TMB was correlated with high DNA repair deficiency, another candidate for ICIs response predictor [ 58 , 59 ]. Singal et al analysis of the clinogenomic database showed differences regarding TMB among distinct driver mutations.…”
Section: Molecularly Targeted Therapies and Immunotherapeutics In Nsc...mentioning
confidence: 99%